2019
DOI: 10.1016/j.bbamcr.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

From APOBEC to ZAP: Diverse mechanisms used by cellular restriction factors to inhibit virus infections

Abstract: Antiviral restriction factors are cellular proteins that inhibit the entry, replication, or spread of viruses. These proteins are critical components of the innate immune system and function to limit the severity and host range of virus infections. Here we review the current knowledge on the mechanisms of action of several restriction factors that affect multiple viruses at distinct stages of their life cycles. For example, APOBEC3G deaminates cytosines to hypermutate reverse transcribed viral DNA; IFITM3 alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 243 publications
(305 reference statements)
0
73
0
1
Order By: Relevance
“…Antiviral restriction factor proteins are part of the innate immune system and function to limit the host range and severity of virus infections (Chemudupati et al, 2019). Zinc-finger antiviral protein (ZAP) is a broad-spectrum antiviral restriction protein first characterized by its ability to inhibit murine leukemia virus replication in rat cells (Gao et al, 2002) and later found to restrict a wide range of viruses, including alphaviruses, filoviruses, hepatitis B virus, influenza A virus, and retroviruses (Bick et al, 2003;Li et al, 2017;Liu et al, 2015;Mao et al, 2013;M€ uller et al, 2007;Tang et al, 2017;Zhu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral restriction factor proteins are part of the innate immune system and function to limit the host range and severity of virus infections (Chemudupati et al, 2019). Zinc-finger antiviral protein (ZAP) is a broad-spectrum antiviral restriction protein first characterized by its ability to inhibit murine leukemia virus replication in rat cells (Gao et al, 2002) and later found to restrict a wide range of viruses, including alphaviruses, filoviruses, hepatitis B virus, influenza A virus, and retroviruses (Bick et al, 2003;Li et al, 2017;Liu et al, 2015;Mao et al, 2013;M€ uller et al, 2007;Tang et al, 2017;Zhu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding virus-host interactions and immune responses will be critical for explaining the high variation in severity of COVID-19 observed in humans (Zhang, Tan et al, 2020). Type I interferon (IFN) is a critical component of the innate immune system that induces expression of hundreds of genes, many of which encode proteins with antiviral activities that block specific steps in viral replication cycles (Chemudupati, Kenney et al, 2019, Schoggins, Wilson et al, 2011. Among these are genes that encode the IFN-induced transmembrane proteins (IFITMs), including IFITM1, IFITM2, and IFITM3.…”
Section: Introductionmentioning
confidence: 99%
“…When HIV-1 or other viruses cause an infection various proteins in mammalian cells acts as restriction factors although these host factors are generally expressed weakly at infected cells (Chemudupati, et al 2019). Expressing these restriction factors simultaneously might be an alternative strategy for preventing replication of HIV-1.…”
Section: Crispr-cas9 Mediated Systems For Hivmentioning
confidence: 99%